Evaluation of radiological health risk caused by the use of fly ash in cement and concrete production and its storage - Turhan, Şeref; Jamasali, Yusof-den (Informa UK Limited, 2024)
As a result of firing pulverized coal in thermal power plants, enormous amounts of fly ash (FA) are produced as industrial waste. The release into the atmosphere and storage of this industrial waste remains one of the major environmental problems that threaten human health by contributing to air, water, and soil pollution. The recovery and reuse of FA in the construction industry is the only economic solution to the existing problem. In this study, the potential radiological risk caused by the usage of FA in concrete and cement production as a main component and its storage in landfill sites was evaluated for people and works by estimating radiological parameters (activity concentration and alpha index, annual effective doses, and the corresponding excess lifetime cancer risks) based on activity concentrations of terrestrial radionuclides in FA. Also, the radiological risk to the workers working in the FA landfill site was evaluated using the Residual Radioactivity Onsite 7.2 code. The average activity concentrations of terrestrial radionuclides in FA samples from the Tunçbilek lignite coal-fired thermal power plant at Kütahya province of Turkey were measured as 417, 156 and 454 Bq kg-1 for 226Ra, 232Th and 40K, respectively. When using up to 35% by mass of FA in cement and concrete, the average values of the radiological parameters revealed that they were within the recommended safety limits. However, code estimations showed that a regular worker in FA storage would be exposed to a total effective dose rate greater than 3 mSv y-1.
Keywords: Waste Disposal Facilities; Turkey; Construction Materials; Radiation Monitoring; Occupational Exposure; Thorium; Potassium Radioisotopes; Humans; Industrial Waste; Coal Ash; Risk Assessment; Radium; Power Plants